An Evolving Role for DEPTOR in Tumor Development and Progression - Zhiwei Wang; Jiateng Zhong; Hiroyuki Inuzuka; Daming Gao; Shavali Shaik; Fazlul H. Sarkar; Wenyi Wei (Neoplasia: An International Journal for Oncology Research, 2012)
Deregulation of the mammalian target of rapamycin (mTOR) signaling pathway has been found in a variety of human cancers. However, the exact molecular mechanism how the mTOR signaling pathway is regulated remains largely elusive. Recently, DEPTOR was identified as an endogenous mTOR inhibitor that could suppress mTOR activity in vivo. More importantly, accumulated evidence has implicated that DEPTOR plays a pivotal role in the development and progression of human malignances, which could in part be mediated through its inhibitory role toward mTOR. Furthermore, three independent laboratories including our own have demonstrated that the stability of DEPTOR is controlled by the SCFβ-TrCP E3 ubiquitin ligase and deregulated DEPTOR destruction might contribute to hyperactivation of mTOR in pathologic conditions including cancer. This review discusses the recent literature regarding the function of DEPTOR involved in cell growth, apoptosis, autophagy, epithelial-mesenchymal transition, and drug resistance, all of which are associated with the pathogenesis of human cancers. Moreover, we also summarize that targeting DEPTOR may be a novel strategy for achieving better anticancer treatments.